The impact of environmental factors and contaminants on thyroid function and disease from fetal to adult life: current evidence and future directions - Street, Maria E.; Shulhai, Anna-Mariia; Petraroli, Maddalena; Patianna, Viviana; Donini, Valentina; Giudice, Antonella; Gnocchi, Margherita; Masetti, Marco; Montani, Anna G.; Rotondo, Roberta; Bernasconi, Sergio; Iughetti, Lorenzo; et al. (Frontiers in Endocrinology, 2024)
The thyroid gland regulates most of the physiological processes. Environmental factors, including climate change, pollution, nutritional changes, and exposure to chemicals, have been recognized to impact thyroid function and health. Thyroid disorders and cancer have increased in the last decade, the latter increasing by 1.1% annually, suggesting that environmental contaminants must play a role. This narrative review explores current knowledge on the relationships among environmental factors and thyroid gland anatomy and function, reporting recent data, mechanisms, and gaps through which environmental factors act. Global warming changes thyroid function, and living in both iodine-poor areas and volcanic regions can represent a threat to thyroid function and can favor cancers because of low iodine intake and exposure to heavy metals and radon. Areas with high nitrate and nitrite concentrations in water and soil also negatively affect thyroid function. Air pollution, particularly particulate matter in outdoor air, can worsen thyroid function and can be carcinogenic. Environmental exposure to endocrine-disrupting chemicals can alter thyroid function in many ways, as some chemicals can mimic and/or disrupt thyroid hormone synthesis, release, and action on target tissues, such as bisphenols, phthalates, perchlorate, and per- and poly-fluoroalkyl substances. When discussing diet and nutrition, there is recent evidence of microbiome-associated changes, and an elevated consumption of animal fat would be associated with an increased production of thyroid autoantibodies. There is some evidence of negative effects of microplastics. Finally, infectious diseases can significantly affect thyroid function; recently, lessons have been learned from the SARS-CoV-2 pandemic. Understanding how environmental factors and contaminants influence thyroid function is crucial for developing preventive strategies and policies to guarantee appropriate development and healthy metabolism in the new generations and for preventing thyroid disease and cancer in adults and the elderly. However, there are many gaps in understanding that warrant further research.